Elastic–Plastic Mechanical Behavior Analysis of a Nb3Sn Superconducting Strand with Initial Thermal Damage - Zhichao Zhang; Lifan Shi (Applied Sciences, 2022)
It is well known that the parameters of Nb3Sn superconducting strands are strain sensitive, and the internal brittle Nb3Sn filament can easily break under deformations. A temperature difference from the preparation temperature of about 1000 K to the cryogenic working environment of 4.2 K damages brittle Nb3Sn fibers before working. Based on the Curtin–Zhou model, the damage theory for fiber-reinforced composites is utilized to study the influence of filament fractures caused by thermal stress. According to the typical multi-scale geometric of the EAS-Nb3Sn strand (European Advanced Superconductor, EAS), an efficient hierarchical homogenized calculation model considering filament fracture and matrix plasticity was established. In this work, we took the filament fracture caused by both thermal stresses and mechanical loads into consideration using the secant modulus and simultaneously had the impact of the plastic constitutive of the bronze matrix and the copper protective layer. Mechanical parameters, such as the homogenized secant modulus, shear modulus, and Poisson’s ratio in different directions of level scale, were predicted at various temperatures. The elastoplastic mechanical behavior of the strands subjected to axial load was analyzed, and the results were in good agreement with the experiment. The initial thermal fiber fracture has non-negligible effects on the mechanical properties of the EAS-Nb3Sn superconducting strand and play the role in accelerating the increase in fiber breakage.